世界统计手册 2018 年 - United Nations (United Nations, 2019)
The World Statistics Pocketbook 2018 edition is the forty-second in a series of annual compilations of key statistical indicators prepared by the United Nations Statistics Division of the Department of Economic and Social Affairs. Over 50 indicators have been collected from more than 20 international statistical sources and are presented in one-page profiles for 30 world geographical regions and 232 countries or areas. The Pocketbook is organised into 5 sections; general information, economic indicators, major trading partners, social indicators, and environmental and infrastructure indicators. This issue presents data for the economic, social, environmental and infrastructure sections for three reference years - 2005, 2010 and 2018 - when available or the most recent data previous to these years, back to 2000, when it is not. For the general information and major trading partners sections the reference year is 2018 and 2017 respectively, unless otherwise footnoted. The indicators in the profiles cover the following topics: communication, crime, development assistance, education, energy, environment, finance, gender, health, international tourism, international trade, labour market, national accounts, population and migration, price and production indices and science and technology.(Chinese language)